Efficient use of solid and water-soluble fertilizers for corn production in the northern part of the steppe zone of the Ukraine - Onopriienko, Dmytro; Онопрієнко, Дмитро Михайлович (Transilvania University of Braşov, 2020)
A high efficiency of fertigation was established after three years of research at an ordinary chernozem on the production of corn hybrid DКС 4351 instead of traditional mineral fertilizing methods. Nitrates are washed out of the root layer after spreading urea on the soil surface before the cultivation in the spring. The nitrate content in the soil in the last two phases was 16-26% higher than in the 5-6 leaf phase after applying the KAC - 32 solution with a sprayer on the soil surface.The mass of 1000 grains was the highest after several times urea application in dose N200 depending on irrigation rate. The maximum yield of corn grain was obtained by applying urea with rate N200 and КАС - 32 with irrigation water during corn vegetation period. There is a tendency to increase the protein in corn grain during fertigation with urea and КАС - 32. The data obtained show that the combination of irrigation with mineral fertilizer application is an effective way to save energy and material resources, increase the yield and grain quality. Після трьох років досліджень на чорноземі звичайному по отриманню гібрида кукурудзи ДКС 4351 замість традиційних методів мінеральних добрив встановлена висока ефективність фертигації. Нітрати вимиваються з кореневого шару після розподілу сечовини по поверхні грунту перед культивацією навесні. Вміст нітратів в грунті в останніх двох фазах було на 16-26% вище, ніж в фазі 5-6 листків після внесення розчину КАЦ-32 за допомогою розпилювача на поверхню грунту. Маса 1000 зерен була максимальною після декількох разове застосування сечовини в дозі N200 в залежності від швидкості зрошення. Максимальний урожай зерна кукурудзи отримано при внесенні сечовини з нормою N200 і КАС-32 з поливної водою в період вегетації кукурудзи. Спостерігається тенденція до збільшення протеїну в зерні кукурудзи при фертигації сечовиною і КАС-32. Отримані дані показують, що поєднання поливу з внесенням мінеральних добрив є ефективним способом економії енергії і матеріальних ресурсів, підвищення врожайності і якості зерна.
Ефективне використання твердих і водорозчинних добрив для виробництва кукурудзи в північної частині Степової зони України
Keywords: corn; кукурудза; mineral fertilizers; мінеральні добрива; irrigation; зрошення; fertigation; фертигація; yield; врожайність; grain quality; якість зерна